Aut Dedere, aut Judicare: The Extradite or Prosecute Clause in International Law - Claire Mitchell (Graduate Institute Publications, 2009)
The aut dedere aut judicare, or "extradite or prosecute" clause is shorthand for a range of clauses that are almost compulsory in international treaties criminalizing conduct, obliging a State to either extradite or prosecute one accused of the crime the subject of the treaty. The obligation has become increasingly central in the emerging legal regime against impunity and has a role in States' armoury of international criminal enforcement mechanisms. Yet there has been little academic consi...